Preparation of stoichiometric molecularly imprinted polymer coatings on magnetic particles for the selective extraction of auramine O from water. Issue 22 (15th October 2018) - Yang, Wenwu; Muhammad, Turghun; Yigaimu, Aziguli; Muhammad, Kipayem; Chen, Lingxin
Abstract: A novel magnetic molecularly imprinted polymer for the selective recognition of auramine O was rationally designed via screening from a library of nonimprinted polymers. A stoichiometric ratio of functional monomer (itaconic acid) and template molecule (auramine O) was found to be 1.5. Meanwhile, the synthesized SiO2 @Fe3 O4 was modified by 0.5 mol/L hydrochloric acid to facilitate the preparation of magnetic molecularly imprinted polymer particles. Adsorption experiments showed that the magnetic polymer particles exhibited good selectivity, recoveries, and enrichment performance. The stoichiometric imprinted polymers have been employed for the selective preconcentration of auramine O from lake water sample. The high specificity of the stoichiometric imprinted polymers was proven in the extraction of mixture solution of auramine O, auramine O hydrochloride, and chrysoidine, and the recoveries ranged between 99.66 and 108.75% (RSD 2.6–3.7%, n = 3) for lake water. These results suggest that this method is effective and can be successfully applied to the analysis of auramine O in environmental water samples.